A study on comparison of short term three dose antibiotic prophylaxis with conventional prolonged postoperative antibiotic coverage in development of surgical site infections - Konidala, M. V. Saila Suman; Gopalam, Padmaja Rani; Kandati, Jithendra (International Surgery Journal, 2018)
Background: Surgical site infections are still an increasing threat to the surgeons despite advances in techniques of surgery, patient care and sterilization practices. Most of the studies state that pre-operative antibiotic prophylaxis is effective in reducing the risk of wound infection in surgical procedures and has been a standard practice followed in many surgeries. Prolonged administration of prophylactic antibiotic has been associated with development of resistant bacterial strains and predisposes the patient in development of wound infection. The aim of the present study is to study the effectiveness of short term antibiotic coverage during decisive period in prevention of post-operative infection in surgical procedures. Methods: A prospective randomized and comparative study was done for one year with 100 cases divided into two groups A and B. Group A received prophylactic Ceftriaxone three doses intravenously, 12 h before surgery 1st dose, 1h before surgery 2nd dose and third 10h after surgery. Group B received Ceftriaxone twice daily for 5 days after surgery. The two groups were compared for development of SSI and associated risk factors. Results: The mean age of the total study group was 37.11± 12.12 years with 60% of males and 40% females. Overall incidence of SSI in study was 24% with Group A 10% and 14% in group B. Anemia, associated drain, increased BMI and undernourishment was associated risk factors and a statistically significant association was found with these risk factors in present study. Pseudomonas and Methicillin resistant staphylococcus aureus were the isolates in the study. Conclusions: Present study strongly recommends the use of antibiotics during surgery than administration after surgery. More care and proper management of the cases are required with associated risk factors like increased BMI, presence of drain and low Hb%. Large multicentric studies are further required to establish further associated risk factors and to identify the local pathogens and their resistance pattern. Appropriate use of antibiotics can substantially reduce the emergence of resistant pathogens and limit the cost of treatment.